The most demanding passages of play in football competition: a comparison between halves - Casamichana, David; Castellano, Julen; Diaz, Antonio Gomez; Gabbett, Tim J.; Martin-Garcia, Andres (Biology of Sport, 2019)
The purpose of this investigation was to determine the differences between halves in the most demanding passages of play in football players according to playing position and duration-specific activity. Global positioning system data were collected from twenty-three football players from a reserve squad of the Spanish La Liga. A total of 265 individual match half data were analysed across the competitive season. Players were categorised based on positional groups: full-back (FB), central defender (CD), midfielder (MF), offensive midfielder (OMF) and forwards (FW). The most demanding passage of match play was analysed using a rolling average method, where maximal values were calculated for five different time durations (1, 3, 5, 10 min and half completed) using distance (m•min -1 ), high metabolic load distance (HMLD; m•min -1 ) and average metabolic power (AMP; W•kg -1 ) as variables of interest. The differences between the first and second half increased as the rolling duration increased, reaching the greatest difference between halves in the complete half (45 min) in all the variables studied (ES = 0.54 ± 0.15, 0.75 ± 0.15 and 0.76 ± 0.15 in distance, HMLD and AMP). The CDs were the players that presented the greatest differences, and it was in the AMP variable where the greatest differences between the first and second half were found. Large decreases in AMP were found for CD (ES = -1.30 ± 0.36) and moderate decreases were found in AMP for FB (ES = -0.84 ± 0.30) and OMF (ES = -0.78 ± 0.37). These results provide insight into the most demanding passages of play to inform training practices for specific football playing positions.